Determination of Continuity of Sustainable Green Financial Behavior with Mediating Variable of Customer Satisfaction of Generation Z Islamic Bank - Rachmawati, Windasari; Abdul Karim; Moeljono (Journal of Business and Management Review, 2025)
ResearchAims:This study examines the post-usage continuation behavior of Generation Z customers in the green finance sector, focusing on Islamic banks. It explores how environmental consciousness, green bank marketing, and customer satisfaction influence ongoing green finance behavior, guided by the Extended Social Help Theory (SST). Design/Methodology:A questionnaire survey was conducted with Generation Z customers of Islamic banks. Partial Least Squares (PLS) analysis was used to assess the relationships between environmental consciousness, marketing initiatives, customer satisfaction, and green finance behavior. Findings:The study finds that both environmental consciousness and green bank marketing initiatives negatively influence the continuation of green finance behavior, with customer satisfaction acting as a mediator. Psychological reactance plays a significant role in shaping these outcomes. TheoreticalContribution:This research contributes to the application of SST in green finance, offering new insights into how psychological reactance interacts with customer satisfaction to affect green finance behavior. It highlights the role of environmental consciousness and marketing initiatives in sustaining engagement with green finance, an area previously underexplored. Keywords:Green finance, Customer satisfaction, Environmental Consciousness, Green banking marketing initiatives, Psychological reactance